Status Periodontal Anak Usia 8-12 Tahun di Sekolah Dasar Negeri 126 Manado - Mantiri, Amanda N. P.; Wowor, Vonny N. S.; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2018)
Abstract: Periodontal disease is a serious chronic infection that involves the destruction of tooth supporting tissues, including gum, periodontal ligaments, and alveolar bone. It is the second most common dental and oral disease suffered by people in the world after dental caries. According to WHO, age 12 years has been chosen as an age group of global indicators for international comparison and surveillance of disease trends. This study was aimed to obtain the periodontal status of students 8-12 years old at SD Negeri 126 Manado (elementary school). This was a descriptive study with a cross sectional design. Respondents were 76 students obtained by using purposive sampling technique. Data of gum examination of all subjects were obtained by using WHO CPI probe and flat dental mirror and were analyzed univariately and presented in distribution tables. The results showed that 7 students (9.2%) had healthy gums, meanwhile 69 students (90.8%) had unhealthy gums, consisting of 66 students (86.8%) with bleeding gums ≤50%, and 3 students (4%) with bleeding gums ≥51%. Conclusion: Most students in this study had bleeding gum ≤50%. Albeit, some students still had healthy gums.Keywords: students aged 8-12 years, periodontal status, gingival bleeding Abstrak: Penyakit periodontal adalah infeksi kronis serius yang melibatkan penghancuran jaringan pendukung gigi, termasuk gingiva, ligamen periodontal, dan tulang alveolar. Penyakit ini tergolong penyakit gigi dan mulut kedua terbanyak yang diderita masyarakat di dunia setelah karies gigi. Menurut WHO, usia 12 tahun dipilih sebagai kelompok usia indikator global untuk perbandingan internasional dan surveilans kecenderungan penyakit. Penelitian ini bertujuan untuk mengetahui status periodontal siswa usia 8-12 tahun di SD Negeri 126 Manado. Jenis penelitian ialah deskriptif dengan desain potong lintang. Responden penelitian ialah 76 siswa, diambil dengan teknik purposive sampling. Data diperoleh berdasarkan pemeriksaan gingiva terhadap subyek menggunakan probe CPI WHO dan kaca mulut, kemudian diolah dengan cara analisis univariat serta disajikan dalam tabel distribusi frekuensi. Hasil penelitian menunjukkan bahwa 7 siswa (9,2%) memiliki gingiva sehat, dan 69 siswa (90,8%) yang tidak sehat terdiri dari 66 siswa (86,8%) mengalami perdarahan gingiva ≤50%, dan 3 siswa (4%) mengalami perdarahan gingiva ≥51%. Simpulan: Sebagian besar siswa usia 8-12 tahun di SD Negeri 126 Manado mengalami perdarahan gingival ≤50%. Walaupun demikian, sebagian kecil siswa masih memiliki gingiva yang sehat.Kata kunci: anak usia 8-12 tahun, status periodontal, perdarahan gingiva